Psychology, character, Multiple Psikologi Belajar dalam Implementasi Pendidikan Karakter Berbasis Multiple Intelegence Research di Pondok Pesantren Bayt Al Hikmah Kota Pasuruan - arifuddin, alfan; Burhani, A. Roisul (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2021)
Bayt Al-Hikmah is one of the pesantren in Pasuruan city that has an education level starting from junior high school, high school and vocational school. This islamic boarding school has applied the concept of Multiple Intelligence Reasearch (MIR) to all its students, meaning that no student is stupid, all students have their own intelligence. This concept was developed based on the theory from Howard Gardner that the whole child is intelligent. The strategy implemented by the teachers at Pesantren Bayt Al-Hikmah is a strategy that is carried out daily. So IQ is not the only factor for a person to be successful and successful in life. If we look back to the previous time, a high number on the student report card shows how clever they are.